The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1754-4505.2010.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

ARTICLE: Oral health condition and treatment needs of Special Olympics athletes in Nigeria

Abstract: Special Olympics (SO) athletes in many parts of the world were reported to have poor oral health and high unmet treatment needs. This study was carried out to determine the oral health condition and treatment needs of SO athletes in Nigeria and to suggest ways of improving access to oral healthcare. Consenting athletes who participated in SO events in Nigeria from 2007 to 2008 received oral examination and evaluation by trained volunteers, using standardized Special Smiles screening forms and procedures design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 16 publications
6
45
1
Order By: Relevance
“…In the UK over 200,000 adults have profound learning disabilities and/or complex medical conditions with poorer oral health, poorer health outcomes, and poorer access to services compared to the rest of their population [35]. In a study of 112 individuals with DS in Kuwait, higher plaque scores and gingival irritation were found on initial screening which decreased after 3 months of a supervised brushing program in their school [36]. Poor oral health including signs of gingivitis and untreated caries were found by dentists on screenings of 1,286 Special Olympics athletes in Nigeria [37].…”
Section: Greater Risk and Greater Disease Burdenmentioning
confidence: 99%
“…In the UK over 200,000 adults have profound learning disabilities and/or complex medical conditions with poorer oral health, poorer health outcomes, and poorer access to services compared to the rest of their population [35]. In a study of 112 individuals with DS in Kuwait, higher plaque scores and gingival irritation were found on initial screening which decreased after 3 months of a supervised brushing program in their school [36]. Poor oral health including signs of gingivitis and untreated caries were found by dentists on screenings of 1,286 Special Olympics athletes in Nigeria [37].…”
Section: Greater Risk and Greater Disease Burdenmentioning
confidence: 99%
“…Through the quality assessment (Table ), the score ranged from 4 to 7 out of 10 possible points. Of the 16 studies that underwent a risk of bias assessment, eight (50%) were considered to have a moderate risk of bias and eight (50%) were considered to have a high risk of bias …”
Section: Resultsmentioning
confidence: 99%
“…A population sample of 35,732 individuals was enrolled in this review, ranging from 160 to 14,319 athletes. Thirteen articles were cross‐sectional studies, another study was a retrospective, one study did not report the design, and Feldman et al . was a pilot study.…”
Section: Resultsmentioning
confidence: 99%
“…Thriandini et al [29] screened child athletes with a mean age of 13.4 and observed that almost 70% of the athletes had visible untreated caries. Oredugba et al [30) conducted a similar study in Nigeria and reported that 22.4% of the child athletes had untreated caries lesions. Bissar et al [31) evaluated child athletes between 12-17 years in the Special Olympics in Germany and observed a caries prevalence of 58% and a mean DMFT of 2.3.…”
Section: Discussionmentioning
confidence: 95%
“…The studies regarding oral health status of child athletes mainly focus on children with intellectual disabilities [29][30][31][32]. Thriandini et al [29] screened child athletes with a mean age of 13.4 and observed that almost 70% of the athletes had visible untreated caries.…”
Section: Discussionmentioning
confidence: 99%